local wisdom photos as adapted materials in teaching english - widiyati, elok (Jurnal Ilmiah Lingua Idea, 2017)
Studentsâ text books mostly contain the materials which do not show the local wisdom and also they do not include sufficient language elements as one of the keys in English learning. So that is why teachers have to innovate the teaching materials in order to combining the language skills, language elements, as well as the local wisdom. Adaptation is one of the most effective innovation which can be done by the teachers to integrate between teaching materials and studentsâ sociocultural condition. Hence, it is very important for them in adjusting the teaching material to the studentsâ internal and external factors. The teachers can choose certain local wisdom to be inserted in their teaching materials in this qualitative study such as tourism, culinary, and batik. Those materials can be downloaded from the internet and the usage should be considered to the language skills and studentsâ grade.